High Dose Risperidone Intoxication in a Patient with Autism Spectrum Disorder - Özdeş, Selma Tekeş; Yazıcı, İpek Perçinel; Yazıcı, Kemal Utku; Öztürk, Şükrü Kaan (Galenos Publishing House, 2023)
Risperidone is an often-preferred molecule for target symptoms in autism spectrum disorder (ASD) patients. Although generally well tolerated, its widespread use in children and adolescents entails the risk of overdose in some cases, intentionally or unintentionally. Pediatric cases related to this issue are rare but can be severe. In this article, a nine year old patient diagnosed with ASD, who was brought to the emergency after unintentionally ingesting high-dose risperidone drug (100 mg), is presented. As far as our can knowledge in the literature, our case is the second highest dose of acute risperidone ingestion seen in a pediatric case. © 2023, Galenos Publishing House. All rights reserved.
Otizm Spektrum Bozukluğu Tanılı Bir Olguda Yüksek Doz Risperidon İntoksikasyonu
Keywords: autism spectrum disorder; child; extrapyramidal adverse effect; poisoning; Risperidone